Composition and abundance of shrimp species (penaeidea and caridea) in Fortaleza Bay, Ubatuba, São Paulo, Brazil - Fransozo, A.; Costa, R. C.; Mantelatto, FLM; Pinheiro, MAA; Santos, S. (Kluwer Academic/plenum Publ, 2002)
The abundance and spatio-temporal distribution of the caridean and penaeid fauna from Fortaleza Bay, Ubatuba, São Paulo, Brazil, were analyzed. Seven transects were sampled over a one year period from November 1988 to October 1989. A total of 17047 shrimps were captured, representing 13 species belonging to 5 families. The interaction of temperature and type of sediment was fundamental in determining the presence and abundance of shrimp species in the area.